Many-body perturbation calculation of spherical nuclei with a separable monopole interaction - Stevenson, P; Strayer, MR; Stone, JR (2001)
We present calculations of ground state properties of spherical, doubly closed-shell nuclei from 16O to 208Pb employing the techniques of many-body perturbation theory using a separable density-dependent monopole interaction. The model gives results in Hartree-Fock order that are of similar quality to other effective density-dependent interactions. In addition, second and third order perturbation corrections to the binding energy are calculated and are found to contribute small, but non-negligible corrections beyond the mean-field result. The perturbation series converges quickly, suggesting that this method may be used to calculate fully correlated wave functions with only second or third order perturbation theory. We discuss the quality of the results and suggest possible methods of improvement.